How Family Capital Influences Responses to the "Double Reduction" Policy (Journal of humanities and social sciences exploratio, 2025)
This article explores the mechanism of how family capital influences the response to the "Double Reduction" policy from the perspective of economic, cultural, and social capital. It analyzes the technological evolution in three dimensions: resource allocation, educational choices, and policy adaptation. The article delves into the key factors and their effects at each stage, including the gradual transmission from basic resource distribution to educational decision-making. At the same time, it analyzes the main challenges currently faced in policy response and proposes opportunities for optimizing policy implementation, such as enhancing policy support, promoting educational equity, advancing digital transformation, and empowering families. Through the effective use of these measures, it is possible to improve policy execution, promote the rational allocation of educational resources, and enhance overall education quality.
Keywords: family capital; Double Reduction policy; policy response; educational equity; influence mechanism